The Effect of Adding Katuk Leaf Puree (Sauropus Andrygynous) in Making Milk Sponge on Physical Properties and Consumer Acceptability - Efrina, Thanty; Yeni Yulianti, Mariani (Politeknik Siber Cerdika Internasional, 2024)
This study aims to analyze the effect of adding katuk leaf puree in making milk sponge on the physical properties and acceptability of consumers. The research location is in the Food Processing Laboratory of the Culinary Education Study Program, Faculty of Engineering, Jakarta State University. The study time starts from August 2021 to September 22, 2023. The research design used was experimental. The population in this study was Culinary Management students who had attended organoleptic courses. The assessment aspect in this study consisted of color, texture, aroma, taste of katuk leaves, and sweetness. The research sample used a random sampling technique with a total of 30 students. The research data used products and questionnaires filled out by panelists. The data analysis techniques used are the Friedman test and the Tuckey test. The best sample of milk sponge with the addition of katuk leaf puree according to expert panelists is with a percentage of 3% as many as 4 panelists (80%) and a percentage of 6% as many as 1 panelist (20%). The results showed that aspects of color, texture, aroma, taste of katuk leaves, and sweetness tended to be liked by panelists. Based on all aspects, the assessment of milk sponge with the addition of 3% katuk leaf puree has the highest average with a score of 3.8 to 4.6. While milk sponge with the addition of 6% katuk leaf puree with a score of 3.4 to 3.8.